Aluminum matrix texture in Al–Al3Ti functionally graded materials analyzed by electron back-scattering diffraction. (22nd December 2015) - Watanabe, Yoshimi; Sequeira, Paulo D.; Sato, Hisashi; Inamura, Tomonari; Hosoda, Hideki
Abstract: Al matrix functionally graded materials (FGMs) with oriented Al3 Ti platelets were fabricated by a centrifugal solid-particle method. The applied centrifugal forces were 30, 60, and 120 G (units of gravity). The orientation and volume fraction gradients of the Al3 Ti platelets within the samples were measured. Since a good lattice correspondence was reported for the close-packed directions and the close-packed planes between Al and Al3 Ti, the Al matrix in the Al–Al3 Ti FGMs fabricated by the centrifugal solid-particle method should have some texture. Al matrix texture was, therefore, analyzed by electron back-scattering diffraction (EBSD). Analysis of the resulting pole figures indicates a preferred orientation along the (200) plane for the Al matrix crystals. Furthermore, increasing the applied centrifugal force enhances the orientation effect. A correlation appears to exist between platelet orientation and the preferred texture of the Al matrix.